A plan of the city & harbour of Louisburg : shewing that part of Gabarus Bay in which the English landed, also their encampment during the Siege in 1745. ([Gentleman's magazine], 1758)
Relief shown pictorially. From: The Gentleman's magazine, v. 28, March 1758. Inset: A map of the island of Cape Breton. Scale [ca. 1:2,000,000]. 18 x 11 cm. Scale [ca. 1:37,000]